2021
DOI: 10.1101/2021.04.09.439239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sub-millisecond conformational transitions of short single-stranded DNA lattices by photon correlation single-molecule FRET

Abstract: Thermally-driven conformational fluctuations (or 'breathing') of DNA plays important roles in the function and regulation of the 'macromolecular machinery of genome expression.' Fluctuations in double-stranded (ds) DNA are involved in the transient exposure of pathways to protein binding sites within the DNA framework, leading to the binding of functional and regulatory proteins to single-stranded (ss) DNA templates. These interactions often require that the ssDNA sequences, as well as the proteins involved, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Additionally, in recent work by Marcus, von Hippel, and co-workers in which they performed single molecule studies of Cy3−Cy5 pairs attached to single-strand-duplex DNA junctions, they demonstrated the tendency for singlestranded DNA segments to adopt configurations that could be grouped into three sets, or macrostates, which they described as compact, partially extended, and fully extended. 66 The restricted and extended bubble configurations we propose to explain the additional aggregate and monomer subpopulations observed here may be consistent with this interpretation of discrete, thermally accessible, transient dye−dye configurations.…”
Section: ■ Discussionsupporting
confidence: 87%
“…Additionally, in recent work by Marcus, von Hippel, and co-workers in which they performed single molecule studies of Cy3−Cy5 pairs attached to single-strand-duplex DNA junctions, they demonstrated the tendency for singlestranded DNA segments to adopt configurations that could be grouped into three sets, or macrostates, which they described as compact, partially extended, and fully extended. 66 The restricted and extended bubble configurations we propose to explain the additional aggregate and monomer subpopulations observed here may be consistent with this interpretation of discrete, thermally accessible, transient dye−dye configurations.…”
Section: ■ Discussionsupporting
confidence: 87%
“…87,88 Beyond strand displacement reactions, the dependence of the photophysics on the complementary central crossover strand has the potential to enable studies of DNA hybridization and other properties of nucleic acids. 89 Finally, the DNA scaffold means that the construct is biocompatible and easily functionalized for specific conjugation to desired targets.…”
mentioning
confidence: 99%